The morphology of the X-ray afterglows and of the jetted GeV emission in long GRBs. Issue 4 (26th March 2021) - Ruffini, R; Moradi, R; Rueda, J A; Li, L; Sahakyan, N; Chen, Y-C; Wang, Y; Aimuratov, Y; Becerra, L; Bianco, C L; Cherubini, C; Filippi, S; et al.
ABSTRACT: We recall evidence that long gamma-ray bursts (GRBs) have binary progenitors and give new examples. Binary-driven hypernovae (BdHNe) consist of a carbon–oxygen core (COcore ) and a neutron star (NS) companion. For binary periods ∼5 min, the COcore collapse originates the subclass BdHN I characterized by (1) an outstanding supernova (SN; the ' SN-rise '); (2) a black hole (BH), born from the NS collapse by SN matter accretion, leading to a GeV emission with luminosity L_GeV = A_GeV t^-α _GeV, observed only in some cases; and (3) a new NS (νNS), born from the SN, originating from the X-ray afterglow with L_ X = A_X t^-α _X, observed in all BdHN I. We record 378 sources and present for four prototype GRBs 130427A, 160509A, 180720B, and 190114C: (1) spectra, luminosities, SN-rise duration; (2) A X, αX = 1.48 ± 0.32, and (3) the νNS spin time evolution. We infer (i) A GeV, αGeV = 1.19 ± 0.04 and (ii) the BdHN I morphology from time-resolved spectral analysis, three-dimensional simulations, and the GeV emission presence/absence in 54 sources within the Fermi -Large Area Telescope boresight angle. For 25 sources, we give the integrated and time-varying GeV emission, 29 sources have no GeV emission detected and show X/gamma-ray flares previously inferred as observed along the binary plane. The 25/54 ratio implies the GeV radiation is emitted within a cone of half-opening angle ≈60° from the normal to the orbital plane. We deduce BH masses of 2.3–8.9 M⊙ and spin of 0.27–0.87 by explaining the GeV emission from the BH rotational energy extraction, while their time evolution validates the BH mass–energy formula.